O existir da enfermagem cuidando na terminalidade da vida: um estudo fenomenológico - Almeida, Carla Simone Leite de; Sales, Catarina Aparecida; Marcon, Sônia Silva (Revista da Escola de Enfermagem da USP, 2014)
By taking care of cancer patients in their process of end of life, nursing experience situations of suffering before the anguish of others. This study aimed to understand the meaning and significance attributed by the nurses from the palliative care cancer hospital. This is a phenomenological research, grounded in Heidegger’s thinking, performed with 13 nurses, who work at Oncology hospitalward, through semi-structured interviews, which were analyzed according to the steps recommended by Josgrilberg. From understanding the statementsof the subjects, two ontological themesemerged: Feeling satisfaction and love in the care offered and Feeling anger and inabilitytowards terminally ill patients.We inferred that working in Oncology Ward is something rewarding for these professionals, but it entails physical and mental suffering, from feeling helpless before the death-dying process. Thus, we showedthat nursing professionals need to be recognized as human beings and as such, also deserving of care.